M.A.J. Trade Engineering / Ahmad Faris Ramli - Ramli, Ahmad Faris (Faculty of Civil Engineering, 2017)
This internship report has 4 chapters which include two month of my internship at M.A.J Trade & Engineering, Melaka. The content of all chapters was broadly explained. This report was wrote according to the format given by coordinator of industrial training, Sir Firdaus bin Akhbar. Firstly, students give details about the company background including vision and mission. M.A.J. Trade & Engineering is a specialist in sport facility maintenance in Malaysia. There are less than 10 company that are possible to run the business. Second chapter is the chapter that explains about my overall internship activity in 8 weeks. In this chapter I had recorded all activities that my company had been run in 8 week. It will explain precisely about the skills, technique and experience that I acquire at M.A.J. Trade & Engineering including overall aspect of civil engineering such as structure, management and geotechnical aspect. On the third chapter I had explained about the projects that I have carried during my industrial training. Besides, in this chapter I also explains about my experience on how to deals with problem I have faced during two month of internship. So the final chapter students conclude about the experienced that I have gained during my industrial training at M.A.J. Trade & Engineering. This final chapter students conclude all about the three chapter that the I have write earlier.